The Cook-ed-up Peary-odd-ical dictionary and who's hoot in the best arctic circles . written by degrees by disagreeing fellow of various degrees of fearlessness - Browne, Lewis Allen, 1876-1937. (Boston, J.W. Luce and Company, 1910)
Illus. end-papers. By L.A. Browne and others. Mode of access: Internet.